'We did commit these crimes': Post-Ottoman solidarities, contested places and Kurdish apology for the Armenian Genocide on Web 2.0. (June 2021) - Halstead, Huw
Web 2.0 facilitates the articulation of transcultural solidarities between Armenian, Assyrian, Greek and Kurdish social media users. This has led to a growing trend for some Kurdish users to apologise for Kurdish complicity in Ottoman crimes, most notably the Armenian Genocide. These post-Ottoman solidarities layer different times and places, creating digital palimpsests where fantasies about place can be constructed, but fantasies that remain connected to enduring and historical place identities and concerns about future territorial borders. These multitemporal montages can foster reconciliation between erstwhile antagonists, lead to mutual recognition of shared victimhood, and perhaps even form the basis for a more inclusive sense of shared (lost) place. Yet, these solidarities can also incubate nationalist irredentism and othering. Moreover, they frequently founder on the very notions of territoriality and exclusive place identity that they sometimes seem ostensibly to transcend.